Design Learning: a reflective model - Smith, Dianne; Hedley, P.; Molley, M. (Elsevier Science Ltd, 2009)
In response to the changing university context, a model for the teaching of Interior Design was developed. Traditional lecture/project-based tutorial structures are replaced by an integrated and interactive model. Aimed to address the demands of the contemporary context, while enabling meaningful learning, it has proven to have much potential. The Model is introduced firstly, by outlining a learning strategy, secondly by describing its structure and content, and thirdly, by identifying key aspects of the learning context. Its achievements are also presented, while acknowledging aspects that could be improved. It offers an innovative alternative mode of learning and teaching interior design.